2000
DOI: 10.1021/jp000942q
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies of Solid Nitromethane

Abstract: A classical potential to simulate the dynamics of a nitromethane crystal as a function of temperature and pressure is described. The intramolecular part of the potential was taken as superposition of bond stretching, bond bending, and torsional angles terms. These terms were parametrized on the basis of the geometric and spectroscopic (vibrational frequencies and eigenvectors) data obtained using ab initio molecular orbital calculations performed at the B3LYP/6-31G* level on an isolated molecule. The intermole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
124
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(139 citation statements)
references
References 31 publications
15
124
0
Order By: Relevance
“…We found that the potential predicts the right order of stability for different phases of HNIW (e > ß > y) crystals in agreement with experimental measurements. 4 At 300 K, the average lattice dimensions agree very well with experimental values, with the corresponding differences for the individual cell edge lengths being no more than 1.0% for the e-polymorph, 0.9% for the /5-polymorph, and 2.5% for the y-polymorph. For the <=-and /-phases, the variations of the unit cell angle ß from the experimental values are 1.3% and 0.1%, respectively, while the other two angles of the unit cell remain approximately equal to 90°.…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…We found that the potential predicts the right order of stability for different phases of HNIW (e > ß > y) crystals in agreement with experimental measurements. 4 At 300 K, the average lattice dimensions agree very well with experimental values, with the corresponding differences for the individual cell edge lengths being no more than 1.0% for the e-polymorph, 0.9% for the /5-polymorph, and 2.5% for the y-polymorph. For the <=-and /-phases, the variations of the unit cell angle ß from the experimental values are 1.3% and 0.1%, respectively, while the other two angles of the unit cell remain approximately equal to 90°.…”
Section: Introductionsupporting
confidence: 69%
“…The recently developed explosive 2,4,6,8,10, can be described as a bridged pair of RDX molecules, suggesting that the intermolecular forces for HNTW might be similar to those of RDX. To explore this possibility, we performed MP and NPT-MD simulations 2 for three of the polymorphs of HNIW (ß-, e-, and y-phases) at ambient pressure and over the temperature range 4.2 to 425 K using the form of potential used in the RDX study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable amount of theoretical work has been performed using classical and quantum molecular dynamics simulations under various conditions. 11,12,[18][19][20] By using classical interatomic potential molecular dynamics simulations, Sorescu et al 11 predicted the structural properties of nitromethane crystals. The thermal decomposition of nitromethane was investigated using Car-Parrinello molecular dynamics simulations, which reveals that it undergoes a thermal decomposition at 2200 K with the cleavage of the C-N bonds.…”
Section: Introductionmentioning
confidence: 99%
“…5-10 a) wuha@ustc.edu.cn b) sluo@pims.ac.cn Theoretical or simulation studies on condensed-phase energetic materials employ such techniques as static electronic structure, [11][12][13][14] molecular dynamics (MD) simulations using empirical or electronic-structure-based force fields, [15][16][17] as well as reactive force fields (ReaxFF), 18,19 and ones based on coarse-grained (CG), particle-based methods. [20][21][22][23] The energetic materials explored include nitromethane, 11,15,16,[24][25][26][27][28][29] octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine (HMX), [30][31][32][33][34] hexa-hydro-1,3,5-trinitro-1,3,5-triazine (RDX), 18,[35][36][37][38][39][40][41][42] 1,3,5-triamino-2,4,6-trinitrobenzene (TATB), 12,13 and pentaerythritol tetranitrate (PETN), 23 among others. 14 See Rice and Sewell 43 for a recent review on this subject.…”
Section: Introductionmentioning
confidence: 99%